Episodic Presentations of Pustular Pyoderma Gangrenosum in PLHIV: A Case Report and Brief Review of Literature - Vijayashree Gokhale; Ponvijaya M. Yadav; Mahabir P. Mishra; Giduturi Naga Lakshmi Vineetha (Wolters Kluwer Medknow Publications, 2024)
We report a case of a 54-year-old female diagnosed with HIV and antiretroviral therapy (ART) for the same. Seven years ago, she suffered from fever, cough and weight loss, was diagnosed with pulmonary tuberculosis and also seropositive for HIV. She suffered from Herpes Zoster infection, after which her ART regimen was changed to TLD (tenofovir, lamivudine and dolutegravir). The patient presented with two episodes of pyoderma gangrenosum (PG), which were biopsy-proven, corresponding to a rise in CD4 counts above 500. She responded to glucocorticoids, both systemic and topical.